Implementasi Kontrol PID untuk Percepatan Rotasi pada Robot Hexapod - Yovi Pratama; Muhammad Irwan Bustami; Afrizal Nehemia Toscany; Chindra Saputra; Xaverius Sika; Janu Hadi Susilo; Arahmad Taupiq; Cahyana Putra Pratama (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
In the development of robot technology, the hexapod robot has great potential to be used in post-disaster rescue because of its ability to adapt to difficult terrain. In this study the authors consider the effectiveness of PID (Proportional Integral Derivative) control based on related literature. Several previous studies have shown the successful use of PID in servo or robotics movement control in different contexts, such as approaching fire sources, controlling DC motor angles, controlling cleaning robot movements on glass, and so on. But the authors want to implement PID motion control with a different approach. The main objective of the hexapod robot is to save the victim by overcoming obstacles and delivering them to the safe zone. In the first test the authors use the PID control method in the middle position between the initial compass rotation value and the destination rotation. The results show that the time needed to reach the rotation goal is relatively fast. In contrast, the second test using the PID control method for all rotary motion resulted in a significant reduction in the error value compared to the first test. Although it requires more time, this method increases the robot's accuracy in achieving the rotation objective efficiently. The robot uses a CMPS03 compass sensor which can provide a direction value which will be input to the PID and servos that are installed as foot movers, each servo is controlled by a microcontroller with the inverse kinematic method to produce the appropriate movement. The results of this research are expected to be the basis for the development of more capable and reliable robots in the next Indonesian SAR robot contest.